Strength through science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The Research and Development Forum for Science-Led Development in Africa (RANDFORUM) is a new initiative which has been established by the International Centre of Insect Physiology and Ecology (ICIPE), the African Academy of Sciences (AAS) and the...